Sistem Keamanan E-Voting Menggunakan Arsitektur Publik Blockchain Ethereum - Vipkas Al Hadid Firdaus; Adei Ismail; Kadek Suarjuna Batubulan; Abiyyu Yafi; Putra Prima Arhandi (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
General elections are a procedure for selecting leaders in a democratic country. However, during the General Election, the vulnerability to vote manipulation is one of the growing issues. Currently, e-voting systems allow hackers to control the system and tamper with election results. In addition, an election process system that is not transparent is difficult to supervise jointly. In this article, a prototype of a general election application is proposed in the voting phase, collecting vote results at each polling station and vote recapitulation. This research uses the blockchain concept with the Ethereum platform. The e-voting system applies smart contracts on the public Ethereum blockchain network. The aim is to maintain the security of election results data and maintain voter confidentiality by using an Ethereum address that represents one voter. In addition, by using the Ethereum public blockchain network, the election process can be monitored jointly. The results obtained in the research conducted in this paper show how the application of blockchain can maintain data integrity by showing the value of the data